How Childhood Obesity May Be Harming Your Child’s Vision: A Systematic Review of High Myopia in Obese Children and Adolescents: Oral Presentation - Observational Study - General practitioner - Ajeng Kartika; Seruni Hanna Ardhia; Marcelius Patria Prabaniswara; Sarah Shabrina; Rona Ali Badjrai (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : High myopia is a severe and progressive form of myopia that can result in blindness. The prevalenceof high myopia is rising globally, and obesity has been identified as a potential risk factor, particularly in children and adolescents. This review aims to evaluate complex interplay between obesity and myopia in the young population. Methods : A systematic literature review was conducted through PubMed, Embase, and Cochrane databases using relevant keywords. Abstract-only papers, case reports/series, and review studies were excluded, and only studies published in English between 2019 - 2023 were considered. The study selection process will be presented according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram. Results : This review analyzed four studies that involved 1.326.898 participants aged between 5 to 19 years. The majority of the studies found a significant association between obesity and high myopia (p<0.05). One of the studies reported that individuals with a normal BMI have a 40% lower risk of developing high myopia compared to those who are obese. Additionally, one study found that even a slightly higher BMI value, which is not yet categorized as obesity, was significantly linked to high myopia (OR 1.19; p=0.009). Conclusion : Most of the studies showed a significant association between high myopia and higher BMI, especially in cases of obesity. However, to establish a deeper understanding of the potential link between high myopia and obesity, further studies are necessary to consolidate data from a larger population and investigate the underlying pathological pathway.